The Role of Artificial Intelligence in Immigration Law Enforcement: Balancing Efficiency, Transparency, and Ethical Accountability - Muhammad Arief Hamdi; Bobby Briando; Faisal Santiago (Yayasan Adra Karima Hubbi, 2024)
Background. The integration of Artificial Intelligence (AI) in immigration law enforcement has significantly improved efficiency in areas such as fraud detection, border security, and visa application assessments. However, the implementation of AI raises critical concerns related to transparency, fairness, and ethical accountability. The